2023
DOI: 10.1155/2023/3286330
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni Modulates Reactive Oxygen Species Production and NADPH Oxidase 1 Expression in Human Intestinal Epithelial Cells

Abstract: Campylobacter jejuni is the major bacterial cause of foodborne gastroenteritis worldwide. Mechanistically, how this pathogen interacts with intrinsic defence machinery of human intestinal epithelial cells (IECs) remains elusive. To address this, we investigated how C. jejuni counteracts the intracellular and extracellular reactive oxygen species (ROS) in IECs. Our work shows that C. jejuni differentially regulates intracellular and extracellular ROS production in human T84 and Caco-2 cells. C. jejuni downregul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The dampening seemed more efficient in human cells (~2/3 of the basal ROS levels) than in chicken macrophages (~half only). Mirroring these data, other C. jejuni strains also moderated ROS induction in human intestinal epithelial cells (Hong et al, 2023 ) and the reduction was linked to decreased transcription of Nox1. Our H 2 O 2 exposure data showed that C. jejuni is not overly sensitive to short‐term and limited oxidative stress and that the capsule and the heptose only provide limited protection.…”
Section: Discussionmentioning
confidence: 86%
“…The dampening seemed more efficient in human cells (~2/3 of the basal ROS levels) than in chicken macrophages (~half only). Mirroring these data, other C. jejuni strains also moderated ROS induction in human intestinal epithelial cells (Hong et al, 2023 ) and the reduction was linked to decreased transcription of Nox1. Our H 2 O 2 exposure data showed that C. jejuni is not overly sensitive to short‐term and limited oxidative stress and that the capsule and the heptose only provide limited protection.…”
Section: Discussionmentioning
confidence: 86%
“…This section delves into the specific disruptions induced by C. jejuni, including increased intestinal permeability, immune system dysregulation and their consequential roles in the pathogenesis of PI-IBS. Upon attachment and invasion into human intestinal epithelial cells (IECs), C. jejuni manipulates the host's cytoskeletal regulation to optimize its invasive capabilities [31]. After successfully invading, C. jejuni is found within cytoplasmic compartments termed Campylobacter-containing vacuoles (CCVs) [31].…”
Section: Campylobacter Jejuni-induced Disruptions: Intestinal Permeab...mentioning
confidence: 99%
“…Upon attachment and invasion into human intestinal epithelial cells (IECs), C. jejuni manipulates the host's cytoskeletal regulation to optimize its invasive capabilities [31]. After successfully invading, C. jejuni is found within cytoplasmic compartments termed Campylobacter-containing vacuoles (CCVs) [31]. Pathogens' virulence factors can compromise the epithelial barrier and enhance intestinal permeability by activating myosin light-chain kinase, which facilitates the degradation of tight junction (TJ) proteins, disrupts actin functionality and triggers apoptosis in intestinal epithelial cells (IECs).…”
Section: Campylobacter Jejuni-induced Disruptions: Intestinal Permeab...mentioning
confidence: 99%